1994
DOI: 10.1073/pnas.91.18.8577
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional photoregulation of cell-type-preferred expression of maize rbcS-m3: 3' and 5' sequences are involved.

Abstract: In the C4 plant maize, members of the rbcS gene family, encoding the small subunit of ribulose-1,5-bisphosphate carboxylase/oxygenase, are not expressed in mesophyll cells (MC) but are expressed strongly in the adjacent bundle sheath cells (BSC). Expression of genes in an in situ transient expression assay indicates that the photostimulated expression seen in BSC during the first 24 h that leaves of dark-grown seedlings are illuminated requires rbcS-m3 sequences lying between -211 bp and +434 bp of the transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
52
2

Year Published

1996
1996
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 29 publications
1
52
2
Order By: Relevance
“…The latter are just beyond the translation stop codon within the 3Ј transcribed region of the gene, but are equally effective when relocated 5Ј to the Ϫ907 to Ϫ445 corepressor-containing region. We also found that expression of the reporter gene is suppressed in MC only after dark-grown seedlings have been illuminated; our observations of suppression were made during the second 24 h of illumination (7). Thus, dark-grown seedlings must be illuminated (in our experiments for 24 h) for the rbcS-m3 repression apparatus to develop.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…The latter are just beyond the translation stop codon within the 3Ј transcribed region of the gene, but are equally effective when relocated 5Ј to the Ϫ907 to Ϫ445 corepressor-containing region. We also found that expression of the reporter gene is suppressed in MC only after dark-grown seedlings have been illuminated; our observations of suppression were made during the second 24 h of illumination (7). Thus, dark-grown seedlings must be illuminated (in our experiments for 24 h) for the rbcS-m3 repression apparatus to develop.…”
mentioning
confidence: 75%
“…We have now identified, within the 3Ј ϩ720 to ϩ957 and the 5Ј Ϫ907 to Ϫ445 bp segments of rbcS-m3 (7,9), three regions that are required for repression. The 3Ј region includes a sequence resembling the repressor form of the binding site for the vertebrate transcription activator-repressor YY1 (Yin Yang 1) (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These studies suggest that transcription initiation may be a mechanism to regulate cell-specific gene expression. However, in vitro studies also suggest an important role for posttranscriptional control of nuclear gene expression (Viret et al, 1994;Purcell et al, 1995). Our finding that Me1 transcripts accumulated throughout a 72-h time course in D-shifted plants, whereas Ppc and RbcS2 transcripts were undetectable after 48 h, suggests that multiple regulatory mechanisms may mediate the cell-specific patterns of photosynthetic gene expression in maize.…”
Section: Influence Of Light Quality On Photosynthetic Differentiationmentioning
confidence: 59%
“…Transient assays in maize M cells have determined regulatory regions of several C4 photosynthetic genes. For example, promoter fusion constructs transiently introduced into maize leaves have defined several important 5Ј regions necessary for light-regulated, cell-specific gene expression of the RbcS2 gene (Schaffner and Sheen, 1991;Bansal et al, 1992;Viret et al, 1994;Purcell et al, 1995). Studies of the Ppc promoter have also revealed regulatory elements required for proper expression (Schaffner and Sheen, 1992;Kausch et al, 2001).…”
Section: Influence Of Light Quality On Photosynthetic Differentiationmentioning
confidence: 99%